Therapeutic Potential of Targeting ß-Arrestin - Bond, Richard A.; Lucero Garcia-Rojas, Emilio Y.; Hegde, Akhil; Walker, Julia K. L. (Frontiers in Pharmacology, 2019)
ß-arrestins are multifunctional proteins that modulate heptahelical 7 transmembrane receptors, also known as G protein-coupled receptors (GPCRs), a superfamily of receptors that regulate most physiological processes. ß-arrestin modulation of GPCR function includes termination of G protein-dependent signaling, initiation of ß-arrestin-dependent signaling, receptor trafficking to degradative or recycling pathways, receptor transactivation, transcriptional regulation, and localization of second messenger regulators. The pleiotropic influence ß-arrestins exert on these receptors regulates a breadth of physiological functions, and additionally, ß-arrestins are involved in the pathophysiology of numerous and wide-ranging diseases, making them prime therapeutic targets. In this review, we briefly describe the mechanisms by which ß-arrestins regulate GPCR signaling, including the functional cellular mechanisms modulated by ß-arrestins and relate this to observed pathophysiological responses associated with ß-arrestins. We focus on the role for ß-arrestins in transducing cell signaling; a pathway that is complementary to the classical G protein-coupling pathway. The existence of these GPCR dual signaling pathways offers an immense therapeutic opportunity through selective targeting of one signaling pathway over the other. Finally, we will consider several mechanisms by which the potential of dual signaling pathway regulation can be harnessed and the implications for improved disease treatments.